The Role of Whistleblowing System and Tax Sanctions in Improving Taxpayer Compliance: Peran Whistleblowing System dan Sanksi Pajak dalam Meningkatkan Kepatuhan Wajib Pajak - Dahlia, Devi Putri; Setiawaty, Agus (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
This research aims to examine the influence of the whistleblowing system and the implementation of sanction on individual taxpayer compliance located in Samarinda Ilir. This study uses the theory of planned behavior to explain the relationships between the variables studied. A quantitative approach was used with primary data obtained through questionnaires. The sample used in this study involved 100 individual taxpayer respondents residing in Samarinda Ilir. The data in this study were analyzed using PLS-SEM through SmartPLS version 4 application. The result of this research show that the whistleblowing system and tax sanctions implementation significantly have a positive effect on taxpayer compliance. This indicates that the more effective the whistleblowing system, the higher the level of individual taxpayer compliance. Moreover, the stricter the tax sanctions imposed, the higher the level of individual taxpayer compliance. This research provides empirical evidence of the importance of establishing a whistleblowing system and enforcing tax sanctions to improve taxpayer compliance.